Sleep quantity and quality in elite youth soccer players: A pilot study - Robey, E.; Dawson, B.; Halson, S.; Gregson, W.; Goodman, C.; Eastwood, P. (European Journal of Sport Science, 2014)
This study examined the effect of early evening high-intensity training on the sleep of elite male youth soccer players (n = 12) using wrist actigraphy. High-intensity training (TRAIN) nights were compared with a home environment (HOME) condition, created by averaging sleep variables on the night before and after TRAIN nights. Additionally, after TRAIN athletes alternately used cold water immersion (TRAIN+CWI) or none, to assess whether cold water immersion (CWI) had any impact on sleep quality and quantity. Ratings of perceived exertion, fatigue and recovery were recorded after training. Actigraphy sleep measures were bedtime, wake time, sleep duration, sleep onset latency, sleep efficiency and wake after sleep onset. Self-rated scores of sleepiness at bedtime and wake, plus overall sleep quality were also recorded. Only fatigue ratings were higher in TRAIN compared to TRAIN+CWI at bedtime, there were no other differences in training data. Both TRAIN and TRAIN+CWI conditions had significant later (07:45 ± 1:09 h p < 0.01 and 07:34 ± 1:20 h p = 0.01) wake times than HOME (06:44 ± 0:41 h). The TRAIN condition had a significantly higher (7 ± 2; p < 0.01) rating of sleepiness at bedtime compared to HOME (6 ± 1), but no further differences were found in any of the sleep (actigraphy and self-reported) measures. Across all conditions, time spent asleep was about 7:30 (±0:52) h:min and sleep efficiency was about 89% (±6.1). In conclusion, early evening high-intensity training had no impact on subsequent sleep quality and quantity, nor was there any effect on sleep after performing CWI post-training.